PENGARUH KETIMPANGAN DAN PENGELUARAN PEMERINTAH TERHADAP TINGKAT KEMISKINAN DI INDONESIA - DARMAWAN, WAWAN; Ichsan, Ichsan (Jurnal Ekonomi Regional Unimal, 2025)
Poverty is one of the most fundamental problems in Indonesia. This is because the poverty rate in Indonesia is still high. This research aims to determine the effect of inequality and government expenditure on the poverty rate in Indonesia. This study uses time series data from 1990 to 2023, using Autoregressive Distributed Lag (ARDL) analysis. The results of the data analysis show that in the short term inequality has a negative and significant effect on the poverty rate, but in the long term inequality has a positive and insignificant effect on the poverty rate. Government expenditure variables in the short and long term have a negative and significant effect on the poverty rate in Indonesia. It is expected that the Indonesian Government can continue to reduce the poverty rate by broadening business opportunities, empowering micro, small, and medium enterprises (MSME) and increasing the level of education in order to improve the quality of human resources which will be able to reduce the poverty rate in Indonesia.